THE IMPACT OF STATUS ANONYMITY ON TEAM DYNAMICS IN CO-CREATION WORKSHOPS. (May 2020) - Lecuna Aguerrevere, A.; Alleblas, J.; Mueller, R. M.; Graves, M.; Thoring, K.
Abstract: This paper looks at the positive effects of partial status anonymity in face-to-face co-creation workshops. Results suggest that especially during the early phases of co-creation, i.e. idea generation, participants experience more freedom to express themselves without self-imposed barriers. We observed positive effects in terms of (1) lowering or even suspending the perceived status among team members, (2) increased motivation, (3) freedom to speak and positive disposition to listen, (4) willingness to consider perspectives from other team members.